Sex-specific socioeconomic inequalities in trajectories of anthropometry, blood pressure, and blood-based biomarkers from birth to 18 years: a prospective cohort study. - O'Neill, Kate N; Ahmed, Minhal; O'Keeffe, Linda M (European Journal of Public Health, 2025)
Evidence on when socioeconomic inequalities in conventional cardiometabolic risk factors emerge and how these change over time is sparse but important in identifying pathways to socioeconomic inequalities in cardiovascular disease (CVD). We examine socioeconomic inequalities in cardiometabolic risk factors trajectories across childhood and adolescence. Data were from the Avon Longitudinal Study of Parents and Children (ALSPAC), born in 1991/1992. Socioeconomic position (SEP) was measured using maternal education from questionnaires at 32-weeks' gestation. Cardiometabolic risk factors measured from birth/mid-childhood to 18 years (y) included fat and lean mass (9–18 y), systolic and diastolic blood pressure (SBP, DBP), pulse rate and glucose (7–18 y), high-density lipoprotein cholesterol (HDL-c), non-HDL-c and triglycerides (birth–18y). Associations were examined using linear spline multilevel models. Among 6517–8952 participants with 11 948–42 607 repeated measures, socioeconomic inequalities in fat mass were evident at age 9 y and persisted throughout adolescence. By 18 y, fat mass was 12.32% [95% confidence interval (CI): 6.96, 17.68] lower among females and 7.94% (95% CI: 1.91, 13.97) lower among males with the highest SEP compared to the lowest. Socioeconomic inequalities in SBP and DBP were evident at 7 y, narrowed in early adolescence and re-emerged between 16 and 18 y, particularly among females. Socioeconomic inequalities in lipids emerged, among females only, between birth and 9 y in non-HDL-c, 7 and 18 y in HDL-c, and 9 and 18 y in triglycerides while inequalities in glucose emerged among males only between 15 and 18 y. Prevention targeting the early life course may be beneficial for reducing socioeconomic inequalities in CVD especially among females who have greater inequalities in cardiometabolic risk factors than males at the end of adolescence.